Rapid‐prototyping and hardware‐in‐the‐loop laboratory platform for development and testing of electro‐mechanical actuator controls. Issue 17 (30th April 2019) - Hogan, Diarmaid; Albiol‐Tendillo, Laura; Kelleher, Brendan; Valdivia‐Guerrero, Virgilio; Foley, Raymond
Abstract : To meet the challenges posed by the increasing use of electrical actuation on board next generation aircraft, advanced experimental testing capabilities are required to investigate optimal system design, performance and control. Rapid control‐prototyping and hardware‐in‐the‐loop (HiL) techniques provide the ability to expedite experimental testing, allowing for elements of the system to be validated without requiring fully realised hardware. Previously, this would require large scale laboratory setups, where the entire electrical and mechanical system would have to be designed and built prior to experimental testing. This study presents the development of a laboratory HiL and rapid‐prototyping test‐bench, capable of investigating the performance of actuator motor control schemes, under a variety of test conditions. Experimental testing is carried out using a laboratory test‐bench, demonstrating the performance of landing gear electromechanical actuator controls under power system and load transients.